Pengaruh Latihan Jump Stop Shoot dan Triple Threat Position Terhadap Hasil Jump Shoot - Rizki Adhi Wijaya; Akor Sitepu; Suranto Suranto (JUPE (Jurnal Penjaskesrek), 2017)
The purpose of this research is to know which is more influence between jump stop shoot exercise and triple threat position to the result of jump shoot. The research method used is experimental method. Samples taken are all students extracurricular basketball in SMA Negeri 2 Pringsewu with the number of 20 people. Data collection techniques used pre-test and post-test. The results of the data analysis obtained tcount XA = -5.48 XB = -3.75 t table -2.101 5% real level, n = 20. If - t table ? t arithmetic ? t table then H0 received Ha rejected, So there is a significant difference in the ability of the initial test and the final test of the Jump Shoot results. While the t-test the difference between XA and XB obtained t-arithmetic -2.24 t table -2.101 then reject H0. The jump stop shoot exercise has a great effect over the exercise of tripple-threat positions on improving the jump shoot result of the extracurricular son of basketball Senior High School 2 Pringsewu. Tujuan dalam penelitian ini adalah untuk mengetahui mana yang lebih berpengaruh antara latihan jump stop shoot dan triple threat position terhadap hasil jump shoot. Metode penelitian yang digunakan adalah metode eksperiment. Sampel yang di ambil adalah seluruh siswa ekstrakurikuler bola basket di SMA Negeri 2 Pringsewu dengan jumlah 20 orang. Teknik pengumpulan data menggunakan pre-test dan post-test. Hasil analisis data diperoleh t-hitung XA = 5,48 XB= 3,75 t tabel-2,101 taraf nyata 5%, n= 20 . Jika - t tabel ? t hitung ? t tabel maka H0 diterima Ha ditolak, Jadi ada perbedaan yang signifikan kemampuan tes awal dan tes akhir terhadap hasil Jump Shoot. Sedangkan uji-t perbedaan antara XA dan XB diperoleh t-hitung -2,24 t tabel-2,101 maka tolak H0. Latihan jump stop shoot memiliki pengaruh yang besar daripada latihan tripple threat position terhadap peningkatan hasil jump shoot pada siswa ektrakulikuler bola basket SMA Negeri 2 Pringsewu.Kata Kunci : jump shoot, jump stop shoot, triple threat position.